1997
DOI: 10.1080/01652176.1997.9694761
|View full text |Cite
|
Sign up to set email alerts
|

The intake of polyunsaturated fatty acids by cats is reflected in their adipose tissue

Abstract: THE INTAKE OF POLYUNSATURATED FATTY ACIDS BY CATS IS REFLECTED IN THEIR ADIPOSE TISSUEM. H. F., van Niell *, and A.C. Beynen2 SUMMARY To find out whether the composition of the subcutaneous adipose tissue of cats reflects the intake of polyunsaturated fatty acids, we performed a feeding trial. Six groups of kittens were fed on diets with variable combinations of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…[10] showed that the ratio of dietary polyunsaturated fatty acids/SFAs was significantly related to the saturated and polyunsaturated content of subcutaneous adipose tissue. van Niel and Beynen also reported a strong correlation in C18:2 and C18:3 levels between diet and subcutaneous adipose tissue in cats [30], as in other species [16, 18, 20, 29]. In our previous trial [14], the fatty acid profile in subcutaneous adipose tissue in experimental and control cats also reflected the dietary fatty acid profile.…”
Section: Discussionmentioning
confidence: 61%
“…[10] showed that the ratio of dietary polyunsaturated fatty acids/SFAs was significantly related to the saturated and polyunsaturated content of subcutaneous adipose tissue. van Niel and Beynen also reported a strong correlation in C18:2 and C18:3 levels between diet and subcutaneous adipose tissue in cats [30], as in other species [16, 18, 20, 29]. In our previous trial [14], the fatty acid profile in subcutaneous adipose tissue in experimental and control cats also reflected the dietary fatty acid profile.…”
Section: Discussionmentioning
confidence: 61%
“…Van Niel & Beynen (69) found strong correlations between the intake of LA (R 0•99), ALA (R 0•99), EPA (R 0•94) and DHA (R 0•91) and their deposition in cutaneous adipose tissue in cats. Dietary concentrations of n-3 fatty acids were shown to determine their deposition in the female reproductive system (follicular fluid, granulosa cells, cumulus-oocyte complex and ovarian tissues) in cattle, ewes, mice and rats, but the biological significance of these findings remains controversial (70) .…”
Section: Discussionmentioning
confidence: 99%
“…Adipose fatty acid signatures have been shown to correlate with dietary fatty acids of assorted prey species in various carnivores including mink (Mustela vison), grey seals (Halichoerus grypus), harp seals (Phoca groenlandica), harbor seals (Phoca vitulina) [Iverson et al, 2004], and domestic cat (Felis catus) [Van Niel and Beynen, 1997]. There is positive correlation between the percentages of polyunsaturated fatty acids in the diet and those in subcutaneous fat of humans, pigs, rats, rabbits, chickens, lambs, nonruminant calves, and cats [Van Niel and Beynen, 1997], although there does seem to be some modification of dietary fats before deposition in polar bears [Grahl-Neilsen et al, 2003]. The fatty acid composition of maternal diet of female mink (Mustela vison) affects the fatty acid composition in milk and kit tissue [Hansen et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…The technique of using tissue fat composition as an index of dietary fat intake has been studied in domestic cats [Van Niel and Beynen, 1997] and marine mammals [Iverson, 1993;Grahl-Nielsen et al, 2003;Iverson et al, 2004]. Adipose fatty acid signatures have been shown to correlate with dietary fatty acids of assorted prey species in various carnivores including mink (Mustela vison), grey seals (Halichoerus grypus), harp seals (Phoca groenlandica), harbor seals (Phoca vitulina) [Iverson et al, 2004], and domestic cat (Felis catus) [Van Niel and Beynen, 1997].…”
Section: Introductionmentioning
confidence: 99%